Gastric Pouch Mixed Adenoneuroendocrine Carcinoma With a Mixed Adenocarcinoma Component After Roux-en-Y Gastric Bypass - Ricardo G. Pastorello MD; Mariana Petaccia de Macedo MD, PhD; Wilson Luiz da Costa Junior MD, PhD; Maria Dirlei F. S. Begnami MD, PhD (SAGE Publishing, 2017)
The Roux-en-Y gastric bypass is one of the most common procedures currently performed for surgical treatment of patients with severe obesity. Gastric cancer after bariatric surgery is not common, with most of them arising in the excluded stomach. Gastric mixed adenoneuroendocrine carcinomas are a rare type of stomach malignancy, composed of both adenocarcinoma and neuroendocrine tumor-cell components, with the latter comprising at least 30% of the whole neoplasm. In this article, we report a unique case of a mixed adenoneuroendocrine carcinoma with a mixed adenocarcinoma (tubular and poorly cohesive) component arising in the gastric pouch of a patient who underwent previous Roux-en-Y gastric bypass for glycemic control. Since stomach cancer is not usual in patients who have formerly undergone bariatric surgery and symptoms tend to be nonspecific, such diagnosis is often rendered at an advanced stage. Full assessment of these patients when presenting such vague symptoms is critical for an early cancer diagnosis.